The Decision to Choose Elderly Residence Based on the Implementation of Servicescape and Elderly Lifestyle Through Brand Image - Emir Fachry; Yuarry Farradia; Sufrin Hannan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to analyze the influence of lifestyle and servicescape on the decision to choose senior housing through brand image. The research method uses a quantitative method using a survey technique. The population used in this study were customers of the RUKUN Senior Living senior housing. The sampling technique is a saturated sample technique with a sample size of 80 respondents. The analysis technique used is descriptive statistical analysis and Structural Equation Modeling (SEM) using Smart PLS 3.0 software. The results of the study show that Lifestyle has a positive and significant effect on brand image (β 0.331, T-value 2.437, P-value 0.015), Servicescape has a positive and significant effect on brand image (β 0.301, T-value 2.530, P-value 0.011), Lifestyle has a positive and significant effect on purchasing decisions (β 0.285, T-value 2.514, P-value 0.012), Servicescape has a positive and significant effect on purchasing decisions (β 0.193, T-value 2.465, P-value 0.014), Brand Image has a positive and significant effect on purchasing decisions (β 0.547, T-value 5.840, P-value 0.000), Lifestyle has a positive and significant effect on purchasing decisions through brand image (β 0.185, T-value 2.235, P-value 0.025), servicescape has a positive and significant effect on purchasing decisions through brand image (β 0.165, T-value 2.347, P-value 0.025).